F18-FLT PET/CT in Patients with Gastric Carcinoma. (25th December 2013) - Małkowski, Bogdan; Staniuk, Tomasz; Śrutek, Ewa; Gorycki, Tomasz; Zegarski, Wojciech; Studniarek, Michał
Abstract : The aim of the study was to evaluate the usefulness of 18F-FLT PET/CT in the detection and differentiation of gastric cancers (GC). 104 consecutive patients (57 cases of adenocarcinoma tubulare (G2 and G3), 17 cases of mucinous adenocarcinoma, 6 cases of undifferentiated carcinoma, 14 cases of adenocarcinoma partim mucocellulare, and 10 cases of end stage gastric cancer) with newly diagnosed advanced gastric cancer were examined with FLT PET/CT. For quantitative and comparative analyses, the maximal standardized uptake value (SUV max ) was calculated for both the tumors and noninvaded gastric wall. Results. There were found, in the group of adenocarcinoma tubulare, SUV max 1.5–23.1 (7.46 ± 4.57 ), in mucinous adenocarcinoma, SUV max 2.3–10.3 (5.5 ± 2.4 ), in undifferentiated carcinoma, SUV max 3.1–13.6 (7.28 ± 3.25 ), in adenocarcinoma partim mucocellulare, SUV max 2–25.3 (7.7 ± 6.99 ), and, in normal gastric wall, SUV max 1.01–2.55 (1.84 ± 0.35 ). For the level of 2.6 cut-off value between the normal wall and neoplasm FLT uptake from ROC analysis, all but five gastric cancers showed higher accumulation of FLT than noninfiltrated mucosa. Conclusion. Gastric cancer presents higher accumulation of 18F-FLT than normal, distended gastric mucosa. Significantly higher accumulation was shown in cancers better differentiated and with higher cellular density.